In-silico homology assisted identification of inhibitor of RNA binding against 2019-nCoV N-protein (N terminal domain). Issue 8 (20th April 2021) - Sarma, Phulen; Shekhar, Nishant; Prajapat, Manisha; Avti, Pramod; Kaur, Hardeep; Kumar, Subodh; Singh, Sanjay; Kumar, Harish; Prakash, Ajay; Dhibar, Deba Prasad; Medhi, Bikash
Abstract: The N terminal domain (NTD) of Nucleocapsid protein (N protein) of coronavirus (CoV) binds to the viral (+) sense RNA and results in CoV ribonucleoprotien (CoV RNP) complex, essential for the virus replication. In this study, the RNA-binding N terminal domain (NTD) of the N protein was targeted for the identification of possible inhibitors of RNA binding. Two NTD structures of N proteins were selected (2OFZ and 1SSK, 92% homology) for virtual screening of 56, 079 compounds from Asinex and Maybridge library to identify top 15 hits for each of the targets based on 'docking score'. These top-hits were further screened for MM-GBSA binding free energy, pharmacokinetic properties (QikProp) and drug-likeness (SwissADME) and subjected to molecular dynamics (MD) studies. Two suitable binders (ZINC00003118440 and ZINC0000146942) against the target 2OFZ were identified. ZINC00003118440 is a theophylline derivative under the drug class 'bronchodilators' and further screening with approved bronchodilators was also studied to identify their ability to bind to the RNA binding region on the N protein. The other identified top hit is ZINC0000146942, which is a 3, 4dihydropyrimidone class molecule. Hence this study suggests two important class of compounds, theophylline and pyrimidone derivaties as possible inhibitors of RNA binding to the N terminal domain of N protein of coronavirus, thus opening new avenues for in vitro validations. Communicated by Ramaswamy H. Sarma